ANALISIS PESAN TOKOH POLITIK LOKAL DI MEDIA SOSIAL TENTANG NILAI-NILAI JAWA DI KABUPATEN MALANG - Bambang Dwi Prasetyo; Moch. Shobastian Mahendra Muchtar (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2026)
This study explores how local political figures in Malang Regency construct Javanese cultural values through political messages on social media, analyzed using Aristotle’s Political Rhetoric framework of ethos, pathos, and logos. The issue is significant given the dynamics of Indonesian digital politics, where cultural symbols increasingly serve as persuasive strategies, especially in communities with strong cultural identities such as the Javanese. Social media has become a key arena for politicians to build legitimacy through cultural representation, though this practice risks reducing cultural meaning into political commodity. Using a qualitative approach, the research applies content analysis to Instagram posts of Aryo Seno Bagaskoro and Rendra Masdrajad Safaat. Data were obtained through online observation and documentation of visual and textual content, then analyzed through reduction, categorization, and interpretation. Findings show that values of andhap asor, rukun, gotong royong, and tepa slira are represented through rhetorical strategies: ethos (moral credibility and politeness), pathos (empathy and emotional closeness), and logos (rational and historical narratives). Yet a shift occurs from substantial ethos to performative ethos, where cultural symbols are instrumentalized to construct political imagery. This study concludes that social media functions as a space of cultural political rhetoric, negotiating tradition and modernity within digital politics.